تأثير التطور الزراعي والصناعي على جودة الحياة في مدينة الوادي -دراسة حالة الملوثات الماء-التربة - هزلة, زينب; مصباحي, ليلى (Université of Eloued, 2019)
This study was conducted to diagnose the state of soil and groundwater contamination in El Oued state. Thus, water samples for irrigation and agricultural soil were collected at the level of three districts of Hassi Khalifa, Kunin, and El Oued (city center). Biochemical analyzes have been carried out on these samples (pH, electrical conductivity, potassium, nitrate, phosphates, lead, copper, manganese, iron, zinc) and we have the results of soil which did not exceed the limit allowed by the World Health Organization. The results show that Iron and lead are one of the most important indicators of water pollution, which change from area to another (agricultural zone, agricultural area, inhabited area). The highest percentage of lead contamination was recorded in the area (Teksebet) with a concentration of 0.130 mg/L ecorded, while the lowest levels of pollution were recorded in an agricultural area (Hassi Khalifa) with a concentration of 0.077 mg/l. In the industrial zone (Kunin), intermediate concentrations of 0.103 mg/l were recorded. The highest percentage of iron contamination was recorded in the agricultural area (Hassi Khalifa) with a concentration of 1.02mg/l ,while the lowest recorded area was in the area (Teksebt) with a concentration of 0.045 mg/L and in the industrial area, (Konin with an average concentration of 0.86 mg/L. Compared to the results of the World Health Organization, these results indicate that the quality of life must be maintained in the context of the risk of environmental and agricultural pollution, which requires proper management and monitoring of the use of agrochemicals
Ecologie et environnement
Keywords: التلوث، جودة الحياة، المعادن ثقيلة، الكيماويات الزراعية ا.; pollution; Quality of life; heavy metal; Agrochemicals.